Implementation of the Projector Augmented-Wave Method: The Use of Atomic Datasets in the Standard PAW-XML Format (Communications in Computational Physics, 2019)
The projector augmented-wave (PAW) method is an important approach forelectronic structure calculations based on the Kohn–Sham density functional theory.And the PAW atomic dataset plays an essential role in the implementation and application of the method. The intensive use of proprietary datasets with limited metadata inprevious years has led to difficulties in both the cross-validation of PAW codes and theunderstanding of the accuracy and transferability of PAW atomic data. In this work,we focus on the open-source ABINIT Jollet–Torrent–Holzwarth (JTH) dataset libraryin the PAW-XML format and investigate the implementation techniques to clarify howthe atomic data participate in the computations. We propose an intermediate datasetthat extends the original PAW-XML one by atomic quantities in derived forms, whichfacilitate the PAW implementation using the JTH library and cover the differences between PAW datasets. Our implementation is validated by comparing the structuralproperty results of representative bulk materials and molecules with those calculatedby ABINIT using the same datasets. Moreover, we discuss the feasibility of using theintermediate dataset for a quick support of PAW-XML datasets in existing PAW code.